Tiskarska in založniška produkcija v luči obveznega izvoda - pregled za obdobje 1991-2006 - Kisovec Trček, Damijana (Knjižnica, 2008)
The paper presents a statistical survey of Slovenian printing and publishing production in the light of legal deposit for the period 1991-2006. The Slovenian printing and publishing production of monographic publications is presented according to accession number and year of publication. The sources of data were accession books of the National and University Library and the local database of the National and University Library in the COBISS system.
Keywords: obvezni izvod; monografske publikacije; printing; tiskarstvo; založništvo; slovenika